The role of the sports press writing highlighting the qualification of Arab teams for the 2018 Russia Football World Cup - moahamed hocine nadhary; namane abdelghani (sports creativity, 2025)
Question of the study: Is there a role of the sports press written in highlighting the qualification of Arab teams for the World Cup Russia 2018 football from the perspective of members of colleges and institutes of physical education and sports? The research Hypothesis: There is no role of the sports press written in highlighting the qualification of Arab teams for the World Cup Russia 2018 football from the perspective of members of colleges and institutes of physical education and sports. The research goals: 1. Defining the importance of sports journalism in transmitting the facts of the World Cup. 2. To highlight the importance of qualifying for the Arab World Cup finals. 3. Developing the treatments that enable the sports press to keep abreast of the development of the media. The Research Areas: The human field: Academics affiliated with colleges and institutes of physical education in the countries (Egypt, Saudi Arabia, Tunisia, Morocco) and 40 academics. 2. Time domain: February-December 2017. 3. Spatial domain: Communicate with the sample via email. The Research Methodology: The researcher used descriptive methodology in this study. The research community is all individuals, events or things that are the subject of the research problem (Shafi'i, Morsi, 1999). The original community consists of academics affiliated with the faculties and institutes of physical education in the four countries qualifying for the World Cup (Egypt, Saudi Arabia, Tunisia, Morocco) Were randomly selected, including 5 academics who were hired for the survey